Analisis Pengembangan Desa Wisata di Sumberdem - Lutfiyah, Silvi; Pardiman, Pardiman; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The location of the village location of Sumberdem is in Wonosari Subdistrict, Malang Regency. the location has the potential to become a tourist destination, and the local government supports the presence of the Tourism Village in this study. to become a tourist destination, and the local government supports the presence of the Tourism Village in this study. The main objective of this research is to analyze the development of Sumberdem Tourism Village. The method of data collection used is a qualitative method which includes documentation and interviews as data collection tools. To improve the quality of data, the quality of researchers using SWOT and PEST data analysis techniques. Furthermore, the researcher used the source triangulation technique to analyze the data. The results of this study are a strategy for the development of a Tourism Village that takes into account internal and external resources. The analysis conducted by this study highlights the potential limitations and strengths of the study. The findings of the study indicate that the research of the Sumberdem Tourism Village still requires the support of various related parties in order to become a legitimate tourism village as well as increasing training and education for the community and Pokdarwis. Keywords: Tourism Village, Development, potential